Effect of Er on thermal property and failure behaviour of LaErZrO thermal barrier coatings. (December 2022) - Shen, Zaoyu; Liu, Guanxi; Huang, Bing; Dai, Jianwei; Mu, Rende; He, Limin
Abstract: This work focuses on the substitution effects of Er on thermal property and failure behaviour of La2 Zr2 O7 . The LaErZrO coatings exhibit the relatively pure pyrochlore phase. The as-deposited coatings exhibit high thermal durability, high thermal expansion coefficient and low thermal conductivity at 1100 °C. After thermal durability test, the failure behaviour is related to the crack evolution and thermally grown oxide growth. Furthermore, the diffusion and concentration of NiCoCrAlYHf might lead to the formation of Ni-Cr-Co-Al oxides and further produce the interface instability along with thermal durability test. Graphical Abstract: ga1 Highlights: The LaErZrO exhibits pyrochlore structure, low thermal conductivity, and high TEC. The LaErZrO coatings with feathery microstructure show high thermal durability. The crack evolution and element diffusion are main reasons leading to TBCs failure. The LaErZrO coatings might be regarded as one advanced TBCs under high temperature.